Spectroscopic investigation of flame synthesized carbon nanoparticle/P3HT blends. (November 2015) - Bruno, A.; Commodo, M.; Haque, S.A.; Minutolo, P.
Abstract: To fulfill the requirement of energy sustainability, organic solar cells (OSCs) should combine the use of solar energy as a renewable energy source with materials that guarantee a clean energy solution based on an evaluation of the full lifecycle from cradle to grave. In this study, we investigated the possibility of using combustion-produced nanoparticles (CPNs) in blends with regioregular poly (3-hexylthiophene) (P3HT), as active layer in OSCs. We present a detailed characterization of the CPNs using Raman spectroscopy, light absorption, cyclic voltammetry and differential mobility analysis, showing their optimal features of band gap and size for use as electron acceptor materials. Moreover we present a spectroscopic investigation of the P3HT:CNPs blends, using static and dynamic fluorescence and transient absorption spectroscopy. P3HT exhibits strong quenching and shortened fluorescence lifetimes when mixed with CNPs. Interestingly, an efficient charge transfer was observed when a high loading of CNPs was added to the blend.